KONFLIK SOSIAL DALAM NOVEL ENTROK KARYA OKKY MADASARI: PENDEKATAN SOSIOLOGI SASTRA - Bondan Wahyu Wulandari; YB Maridja (CARAKA, 2018)
The aims of this research are as follows. 1) Describe the plot, character and characterization, and setting in the novel Entrok. 2) Describe the causes of the conflict in the novel Entrok. 3) Describe the form of conflict in novel Entrok written by Okky Madasari. The type of this research is qualitative. The data of this research are series of events in the form of sentences and paragraphs found in the novel Entrok by Okky Madasari. The source of data is novel Entrok by Okky Madasari. Research instrument used in this research is the researcher itself who already known and learnt the theories of plot, character and characterization, and setting. The technique for collecting the data is conducted by reading and making notes of the data found in th novel Entrok by Okky Madasari. The technique for analysis data was done by using descriptive qualitative technique. The findings of this research are as follows. 1). The plot of the novel Entrok is advance plot. Character and characterization, there are Marni and Rahayu as the main characters, Marni is unswerving of what she believes and hard to accept new things, ill tempred, and hard working while Rahayu is unswerving of what she believes and does not like to lose. The additional characters are Teja who has defeatist attitude, Simbok who always patient and hard working, Mr. Suyat who act as mediator and fair enough with his family, Mrs. Parti and Mrs. Yem whose ill tempered. Moreover, there are Mrs. Dimah who likes to help others, Tonah who is a coward, Mr. Waji whose sly and likes to bad-mounthing other people, and Sumadi whose sly and does not has responsibility. There are also Amri, a well mannered person who has high sense of justice, Koh Cahyadi who devotedly for his parents, Wagimun who does not has faith in himself, Endang Sulastri whose ill tempered and does not has responsibility, and Kyai Hasbi who has high sense of justice. There are three settings in novel Entrok, that are setting of place, setting of time, and the social setting. Seting of time are in Singget village and Magelang. Setting of time are around the year of 1950 through 1999, in the morning, afternoon, and night. The social setting are shown in an era where the life of the citizen still traditional and still believe in mystical, an era when there were conflict in the society, and an era when the country starts to develop. 2). The causes of the conflict in the novel Entrok are the difference of convictions, the difference of culture, and the difference of importance. 3). The form of conflict in the novel Entrok are conflict caused by the difference of individual and conflict caused by the difference in culture.